2 years audit of laparoscopic cholecystectomy performed in Hospital USM and factors related to conversion - Qaris, Iqtidaar (2018)
Introduction: The gold standard for treatment of symptomatic gallstone disease is laparoscopic cholecystectomy which has nowadays replaced open surgery. However around 2-15% of the laparoscopic cases need to be converted to open cholecystectomy for various reasons but it should be noted that conversion to open is neither a failure nor a complication of the surgery but it is just to prevent further complication and for the safety of the patient. Objectives: This study aimed to report number of cases of laparoscopic cholecystectomy performed within 2 years in Hospital Universiti Sains Malaysia, determine the conversion rate and associate this conversion to demographics and patient risk factors which were preoperative ALT, ALP, WCC, ultrasound findings of gallbladder wall thickness, presence of gallstones and postoperative histopathological report. Methods: This was a retrospective study of patients undergoing elective laparoscopic cholecystectomy at Hospital Universiti Sains Malaysia from October 2013 to December 2015. The sample size was calculated using the single proportion formula with a drop out rate of 20%. Patients included in this study were those who were above 18 years of age undergoing elective laparoscopic cholecystectomy in Hospital Universiti Sains Malaysia within the time period mentioned above. The exclusioncriteria were patients less than 18 years, cases suspected or confirmed malignancy, those with incomplete data records, emergency surgeries and finally those cases of laparoscopiccholecystectomies combined with other surgeries under the same setting. The patients’ data were collected from their records and statistical analysis was done using SPSS software. Univariate analysis, Chi-squared test and multivariate analysis for multiple logistic regression were done with a p-value of <0.05 considered as statistically significant. Results: The number of patients fulfilling the inclusion/exclusion criteria involved in this study was 122. The conversion rate of laparoscopic to open cholecystectomy was found to be 11.5%. The mean age of patients in this study was 50.4 years with majority females (70.5%) and of malay race (91.8%). The patients were divided into 2 groups (laparoscopic cholecystectomy and laparoscopic converted to open cholecystectomy) and further statistical analysis was performed. Independent T test used to compare the mean of numerical variables showed no statistically significant difference in age (p = 0.165), preoperative WCC (p = 0.725), ALP (p = 0.078), ALT (p = 0.176). Univariate analysis based on simple logistic regression and multiple logistic regression were also done and noted only gallbladder wall thickness > 4mm to be statistically significant risk factor for conversion of laparoscopic to open cholecystectomy with a p-value of 0.007. Other variables did not give statistically significant results. Ultimately the area under receiver operating characteristic (ROC) curve was 0.678 (95% CI; 0.52,0.84) which indicates satisfactory discriminating power. Conclusion: In this study, the conversion rate of laparoscopic to open cholecystectomy in Hospital Universiti Sains Malaysia for elective cases is 11.5% which is within the acceptable range of 2-15%. Furthermore, based on multiple logistic regression analysis, preoperative gallbladder wall thickness >4mm on ultrasound is the only statistically significant risk factor for conversion of laparoscopic to open cholecystectomy (p-value=0.007, adjusted OR=0.21, 95% CI: 0.07,0.65).